MV-RLU - Jaeho Kim; Ajit Mathew; Sanidhya Kashyap; Madhava Krishnan Ramanathan; Changwoo Min (Proceedings of the Twenty-Fourth International Conference on Architectural Support for Programming Languages and Operating Systems, 2019)
A 74-year-old woman with a pulmonary nodule showing interval growth on follow-up imaging presented with dysphagia and abdominal bloating. 18F-FDG PET/CT displayed a gas-containing subcarinal soft-tissue density with intense FDG uptake and communicating with the adjacent hypermetabolic and focally thickened esophagus. These findings indicated a strong suspicion for esophageal malignancy complicated by fistula formation. Subsequent endoscopy demonstrated a nodular mucosal protrusion with a fistulous opening, revealing no evidence of malignancy. The patient received conservative treatment and clinical improvement. A coexisting left upper lobe ground-glass nodule with mild FDG uptake, unrelated to the esophageal lesion, was suggestive of early adenocarcinoma.